THE MODEL FOR INTEGRATING ROAD FUNCTION, ROAD STATUS, AND ROAD CLASS IN THE ROAD NETWORK SYSTEM - Kurniawan, Herry; Suparma, Latif Budi; Utomo, Suryo Hapsoro Tri (Journal of Applied Engineering Science, 2024)
The lack of synchronization between road categories in Indonesia, which includes road function, road status, road infrastructure class, and road load class, results in negative impacts on roads, including air pollution, traffic accidents, congestion, and road deterioration that occurs more rapidly than the planned road lifespan. Another consequence is that the lack of synchronization between logistics transport trips and road function and classifications can lead to violations of the maximum axle load limits for goods vehicles. The objective of this research is to establish an analytical correlation between the identification of road segments based on road function, road status, road load class, and road infrastructure class, as well as the impact variables. Additionally, the aim is to develop a model for determining road function, road status, road infrastructure class, and road load class, along with their impact variables. The primary areas studied in this research are the road networks in Lampung, DIY, East Java, South Kalimantan, West Papua, Maluku, and Southeast Sulawesi. The research employs two quantitative techniques: Importance Performance Analysis (IPA) and Structural Equation Modelling (SEM). Data and information have been gathered through questionnaire surveys, desk studies, and interviews, which confirm Law No. 2 of 2022 concerning Roads, which explains that road function are derived from road status, while road infrastructure class and road load class are also derived from road function. The findings reveal that how roads are classified by their function has a major effect on traffic outcomes. This emphasizes the importance of categorizing roads based on their intended use. Consequently, it is crucial for planners to focus on functional classifications when designing and managing road infrastructure to tackle traffic issues effectively.
Keywords: road function, road status, road network system, transport integration, structural equation modelling